Caenorhabditis elegans glia modulate neuronal activity and behavior - Stout, Randy F.; Verkhratsky, Alexei; Parpura, Vladimir (Frontiers in Cellular Neuroscience, 2014)
Glial cells of Caenorhabditis elegans can modulate neuronal activity and behavior, which is the focus of this review. Initially, we provide an overview of neuroglial evolution, making a comparison between C. elegans glia and their genealogical counterparts. What follows is a brief discussion on C. elegans glia characteristics in terms of their exact numbers, germ layers origin, their necessity for proper development of sensory organs, and lack of their need for neuronal survival. The more specific roles that various glial cells have on neuron-based activity/behavior are succinctly presented. The cephalic sheath glia are important for development, maintenance and activity of central synapses, whereas the amphid glia seem to set the tone of sensory synapses; these glial cell types are ectoderm-derived. Mesoderm-derived Glial-Like cells in the nerve Ring (GLRs) appear to be a part of the circuit for production of motor movement of the worm anterior. Finally, we discuss tools and approaches utilized in studying C. elegans glia, which are assets available for this animal, making it an appealing model, not only in neurosciences, but in biology in general.